The Dynamics of NS1 Antigen and Platelet Levels in the Acute Phase of Dengue Hemorrhagic Fever - Emma Ismawatie; Ilyas Syafiq Darul Ridzuan; Yulia Ratna Dewi; Sunarti (Sriwijaya Journal of Internal Medicine, 2025)
Introduction: Dengue hemorrhagic fever (DHF) is a significant global health concern, particularly in tropical and subtropical regions. The early diagnosis and effective management of DHF are crucial to reduce morbidity and mortality. The NS1 antigen and platelet count are two key laboratory parameters used in the diagnosis and monitoring of DHF. This study aimed to investigate the dynamics of NS1 antigen and platelet levels during the acute phase of DHF and their correlation with disease severity. Methods: A prospective cohort study was conducted at a tertiary care hospital in Central Java, Indonesia. Patients presenting with suspected DHF were enrolled and followed up during their hospitalization. Blood samples were collected at admission and at regular intervals to measure NS1 antigen levels and platelet counts. Clinical and laboratory data were collected to assess disease severity. Results: A total of 150 patients were included in the study. The majority of patients were adults (median age, 32 years) with a female predominance (58%). The median duration of fever at presentation was 4 days. NS1 antigen levels were significantly higher in patients with DHF compared to those with dengue fever (DF) (p < 0.001). Platelet counts were significantly lower in patients with DHF compared to those with DF (p < 0.001). NS1 antigen levels showed a negative correlation with platelet counts (r = -0.62, p < 0.001). The levels of NS1 antigen and platelet count were also significantly associated with disease severity. Conclusion: The dynamics of NS1 antigen and platelet levels during the acute phase of DHF provide valuable insights into disease pathogenesis and can aid in the early diagnosis and prediction of disease severity. The negative correlation between NS1 antigen and platelet levels suggests a potential role of NS1 in the development of thrombocytopenia in DHF. Further studies are needed to elucidate the exact mechanisms underlying these observations.